The importance of crop residues in the diet of Fulani cattle in the sub-humid zone of Nigeria. Progress report on crop residue determination at Kurmin Biri-Kachia, Kaduna state - Magaji, S.O. (International Livestock Centre for Africa, 1980)
Report that deals with the establishment & determination of yield components of Sorghum & the undersown Stylosanthes species in small farms belonging to settled Fulani pastoralists in the Kurmin Biri-Kachia case study area, Nigeria; includes tables showing residue & sorghum grain yields at early & late Stylosanthes planting, total feed produced (leaf + shaft) at each field and Stylosanthes yields, and comparing residue & sorghum grain yields of undersown & fertilized, undersown only and sorghum alone fields.